Identification of competencies for Malaysian occupational safety and health professionals - Daud, Rabaayah; Ismail, Maimunah; Omar, Zoharah (National Institute of Occupational Safety and Health, 2010)
Competencies of occupational safety and health (OSH) professionals have become a concern due to the significance of safety management in the field of safety engineering. The purpose of this article is to identify competencies needed by OSH professionals. These competencies are required by professionals in administrating and enforcing legislations related to OSH in Malaysia. This study used Delphi technique in three rounds of data collection. The benefits of this research approach are the use of experts in gaining opinions without time and geographical restraints. The results show 25 generic competencies with combinations of cognitive, interpersonal and intrapersonal competencies and 33 functional or specific competencies including knowledge and skills needed by OSH professionals. Both generic and functional competencies are also divided into threshold and differentiating competencies that would be used to differentiate average and excellent performance of OSH professionals.